KARAKTERISTIK JENIS ENDAPAN BERDASARKAN MODEL VARIOGRAM ELEVASI PADA DESA PARDAMEAN AJIBATA KECAMATAN AJIBATA KABUPATEN TOBA SUMATERA UTARA - Akbar, Ade Arriza; Lismawaty; Sedarta (LPPM ISTP, 2023)
Variogram is a measure of variance, Variogram is used to determine the distance where the observed data values become independent or have no correlation. The symbol of the variogram is 2γ. The variogram is a tool in geostatistics that is useful for showing spatial correlations between measured data. Regionalized variables are variables that have different values (vary) with changing locations/places.Exploration or feasibility studies, mine-engineer/geologist are required to be able to understand the characteristics of the value distribution at an affordable and simple cost, especially since the minerals are of low value. According to David (1977), modeling the variogram a distribution of reported values is typical for each type of deposit. The use of surfer software in the application of elevation variograms using GPS and Google Earth elevation data makes comparisons of data between elevation variograms in the study area. The results of the elevation variogram data show a gradual and consistent increase in the upward curve that can be interpreted as a sediment type research field. Field data validation to determine the characteristics of the sediment at the study site. Field conditions have different variations in grain size and lithology but the results of the elevation variogram still show a consistent increase. In the initial exploration stage the variogram method can help determine the type of deposit and changes in the direction of the deposit.